The relationships between cognitive reserve, cognitive functioning and quality of life in first-episode schizophrenia spectrum disorders. (April 2022) - Rodriguez, Mabel; Knížková, Karolína; Keřková, Barbora; Siroňová, Aneta; Šustová, Petra; Jonáš, Juraj; Španiel, Filip
Highlights: Cognitive reserve (CR) may partially explain the heterogeneity of cognition in schizophrenia. In the present study, we explored the relation between CR, cognition and quality of life in patients with first-episode schizophrenia spectrum disorder. CR was calculated from the participants' education, premorbid IQ, and socioeconomic status. In patients, CR was related to all cognitive domains. Higher CR scores were associated with better cognitive performance. CR was negatively related to the social construct of patients' quality of life, and positively to symptom severity, and general functioning. Abstract: Cognitive reserve (CR) has been conceptualized as an individual's ability to optimize or maximize performance through differential recruitment of brain networks. As such, CR may contribute to the heterogeneity of cognitive deficits observed in schizophrenia. This study aimed to assess the relationships between CR, cognition and quality of life in first-episode (FES) patients. A total of 137 patients with either ICD-10 schizophrenia or "acute and transient psychotic disorders" diagnosis, and 62 healthy controls had completed a comprehensive assessment of six cognitive domains: speed of processing, attention, working memory/flexibility, verbal memory, visual memory, and abstraction/executive functioning. CR was calculated from the participants' education, premorbid IQ, and socioeconomic status. The results suggested that in patients, CR was positively related to cognitive performance in all domains, explaining 42.6% of the variance observed in cognition overall. Effects of CR in the control group were limited to three domains: speed of processing, abstraction/executive function and working memory/flexibility. These results suggest that CR largely contributes to cognitive variations present in FES patients. In addition, CR was negatively related to the social construct of patients' quality of life, and positively to symptom severity and general functioning.